2018
DOI: 10.1111/1471-0307.12515
|View full text |Cite
|
Sign up to set email alerts
|

A review on polyphenols: Classification, beneficial effects and their application in dairy products

Abstract: Recently, the number of studies regarding the physiological activities of food‐derived bioactives and food components with functional properties has greatly increased. Many studies have emphasised the beneficial effects of polyphenols regarding their antioxidant, antiproliferative and anti‐inflammatory properties. This study highlights their application in dairy products, notes in which form they are applied and discusses the effects on the physicochemical and sensory characteristics of products, although some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
80
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 94 publications
5
80
0
4
Order By: Relevance
“…However, the evaluators expressed the greatest acceptance of cheese with 5% molten chocolate, either fresh or stored for 2 weeks. These results are in line with a recent review by Cutrim and Cortez () showing that enriching dairy products with high levels of phenols generates unpleasant taste and, consequently, less consumer liking.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, the evaluators expressed the greatest acceptance of cheese with 5% molten chocolate, either fresh or stored for 2 weeks. These results are in line with a recent review by Cutrim and Cortez () showing that enriching dairy products with high levels of phenols generates unpleasant taste and, consequently, less consumer liking.…”
Section: Resultssupporting
confidence: 92%
“…Cutrim and Cortez () reported that various macro‐biomolecules (carbohydrates, proteins, and lipids) have protective effects on polyphenols during gastrointestinal transit, favoring the bioavailability and bioaccessibility of polyphenols as well as their bioactivity. Lamothe, Langlois, Bazinet, Couillard, and Britten () studied the in vitro digestion kinetic of polyphenols from a green tea extract incorporated into dairy matrices, observing improved stability and antioxidant activity due to the formation of a polyphenol–protein complex.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the oral phase, after the oesophagus–stomach step (gastric digestion), the TPC of all the samples (Control, S1 and S2) increased significantly ( P < 0.05) in relation to the nondigested samples, thereby suggesting that gastric digestion conditions improved the release of phenolic compounds from the food matrix, which is in accordance with previous literature data (Rodríguez‐Roque et al . ; Cutrim and Cortez ). According to Saura‐Calixto et al .…”
Section: Resultsmentioning
confidence: 99%
“…). Within this context, natural ingredients derived from plants have been extensively studied for their potential application as natural additives in the food and nutraceutical fields (Cutrim and Cortez ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation